2021
DOI: 10.31849/elt-lectura.v8i1.5920
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Speaking Anxiety in English Education Study Program

Abstract: This study explores speaking anxiety: the identification of speaking anxiety in English education study program. Using a mixed methods approach, this research selected two different categories, students studying in English Education Department private university and those studying in English Education Department in public university as research participants. The findings suggest that the main factors of speaking anxiety causes at public university were essentially affected by nervousness and idea delivery. Nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Due to the survey results, this anxious feeling can be linked to other questions in the survey where students may feel anxious because they are afraid that other students will laugh at them when they speak. This point can also be linked to Syahfutra and Wibowo (2021) who found the main factor of students speaking anxiety were self-confidence; afraid of making mistakes, nervousness, and idea delivery. Santosa (2018) also reported that Indonesian students experience speaking anxiety because they are afraid of making grammatical mistakes and lack of speaking vocabulary.…”
Section: Discussionmentioning
confidence: 95%
“…Due to the survey results, this anxious feeling can be linked to other questions in the survey where students may feel anxious because they are afraid that other students will laugh at them when they speak. This point can also be linked to Syahfutra and Wibowo (2021) who found the main factor of students speaking anxiety were self-confidence; afraid of making mistakes, nervousness, and idea delivery. Santosa (2018) also reported that Indonesian students experience speaking anxiety because they are afraid of making grammatical mistakes and lack of speaking vocabulary.…”
Section: Discussionmentioning
confidence: 95%
“…When we pronounce the words, we make the speaking sound. Speaking is the most challenging aspect of learning the English language for some students, because there are some voices in English that do not exist in Indonesian (Bystrova, 2020;Syahfutra, 2021). For many foreign language learners, learning to speak is quite tough.…”
Section: Introductionmentioning
confidence: 99%
“…Young (1991) & Suhartono, 2022)also stated that learner beliefs about language learning can contribute greatly to creating language anxiety in students. Gynan in (Syahfutra, 2021)added that the most important aspect of L2 learning in learner beliefs about language learning is pronunciation, even though the other close to the other learner aspect, such as vocabulary, communication, travelling to country a country where the language is spoken, translation or making friends. Horwitz cited in (Nurilahi & Suhartono, 2022) presented various kinds of learner beliefs, suggesting that some of them are derived from the learners' irrational and unrealistic learners' such as : 1) some learners were concerned about the correctness of their speech in comparison to native speaker, like accent or pronunciation, 2) some believed that two years is enough time in language learning to achieve a native like fluency, 3) some believed that language learning is learning about how to translate, and 4) some others believed that success of L2 learning limited to a few individuals who are gifted for language learning.…”
Section: Introductionmentioning
confidence: 99%